WHEN RELIGION MEETS THE INTERNET (Cyber-Religion and the Secularization Thesis) - Iqbal, Asep Muhamad (Jurnal Komunikasi Islam, 2016)
This article examines the presence of cyber-religion, the worldwide increasing use of the Internet for religious purposes, in which religion is migrating online as its strategies of adaptation and shaping a new environment. It aims to look at the phenomenon of religious migration to virtual world and its possible implications for secularization thesis. The article argues that the massive emergence of online religion serves a (another) counterpoint to the prediction of the end of religion in modern society as proposed by the proponents of secularization theory. It also claims that religious use of the Internet among religion surfers has no significant impacts on the real world organized religions and their religious communal identity.